2011
DOI: 10.14214/sf.110
|View full text |Cite
|
Sign up to set email alerts
|

Climate for innovation and innovation strategy as drivers for success in the wood industry: moderation effects of firm size, industry sector, and country of operation

Abstract: This study examines the relationships between firm financial performance and a) the climate for innovation and b) innovation strategy in the wood products industry. The focus is on the moderator effects of firm size, country of operation, and industry sector. Using a sample of 460 responses from chief executive officers and top managers of Norwegian and US firms, we conducted a regression analysis to probe for interaction effects. The sample included primary and secondary manufacturers of various sizes. Consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 57 publications
4
34
0
1
Order By: Relevance
“…Many studies have shown that context is very important to engage employees with their job and encourage them to contribute more towards the organization (e.g., (Amabile et al 1996;Gilson and Shalley 2004;Hunter et al 2007;Nybakk et al 2011)). In the organizational literature, thriving reflects the joint experience of vitality and learning, and enables employees to grow continually; for example, Ryff (1989) suggested that when individuals grow, they consider themselves to be expanding in ways that reflect enhanced self-knowledge and effectiveness.…”
Section: Mediating Role Of Organizational Support For Innovationmentioning
confidence: 99%
“…Many studies have shown that context is very important to engage employees with their job and encourage them to contribute more towards the organization (e.g., (Amabile et al 1996;Gilson and Shalley 2004;Hunter et al 2007;Nybakk et al 2011)). In the organizational literature, thriving reflects the joint experience of vitality and learning, and enables employees to grow continually; for example, Ryff (1989) suggested that when individuals grow, they consider themselves to be expanding in ways that reflect enhanced self-knowledge and effectiveness.…”
Section: Mediating Role Of Organizational Support For Innovationmentioning
confidence: 99%
“…The possible moderating effect of firm size is drawn from previous studies showing that firm size can act as a moderator in innovation research (Nybakk, Crispell, & Hansen, 2011;Khan, Rehman, & Fatima, 2009). Khan et al (2009) found that firm size moderates the relationship between transformational leadership and firms' innovativeness.…”
Section: The Moderating Effect Of Firm Sizementioning
confidence: 99%
“…The mentioned studies have all been conducted in the U.S. However, Nybakk et al [51] compared the U.S. wood industry with Norway and found that the innovation climate for innovation's effect on firm performance was consistent, regardless of the country of operation, industry sector, size or country. The similarities in these results could be connected to the fact that the countries have a similar Western culture and wealth status.…”
Section: Organizational Climate/culture For Innovationmentioning
confidence: 99%
“…The similarities in these results could be connected to the fact that the countries have a similar Western culture and wealth status. Results could differ in non-Western countries or post-communist countries transitioning to a market-based economy [51].…”
Section: Organizational Climate/culture For Innovationmentioning
confidence: 99%